A Medium-Scale DSGE Model for the Integrated Policy Framework - Adrian, Tobias (IMF Working Papers; Working Paper ;, 2022)
This paper jointly analyzes the optimal conduct of monetary policy, foreign exchange intervention, fiscal policy, macroprudential policy, and capital flow management. This policy analysis is based on an estimated medium-scale dynamic stochastic general equilibrium (DSGE) model of the world economy, featuring a range of nominal and real rigidities, extensive macrofinancial linkages with endogenous risk, and diverse spillover transmission channels. In the pursuit of inflation and output stabilization objectives, it is optimal to adjust all policies in response to domestic and global financial cycle upturns and downturns when feasible-including foreign exchange intervention and capital flow management under some conditions-to widely varying degrees depending on the structural characteristics of the economy. The framework is applied empirically to four small open advanced and emerging market economies.